Graphene as saturable absorber for photonics applications / Farah Diana binti Muhammad - Muhammad, Farah Diana (2014)
Graphene, a single layer of carbon atoms, is nowadays considered a great candidate to be applied as the saturable absorber (SA) with its desirable optical characteristics such as ultrafast recovery time and ultrawideband absorption due to its zero bandgap energy and linear dispersion of Dirac electrons. With its advantage over semiconductor saturable absorber mirror (SESAM) in terms of the cost, tuning range and ease of fabrication, graphene has been widely accepted to replace the usage of SESAM. In this work, several methods of graphene integration onto the fiber ferrule have been demonstrated, such as by optical deposition method, by sandwiching graphene thin film between the fiber ferrules and by adhering graphene flakes onto the fiber ferrule using index matching gel. The saturable absorption properties of the deposited graphene by each different method is also measured and analysed. Taking advantage of the unique properties of graphene, the graphene deposited in this work has been demonstrated for Q-switching operation in various setup configurations, from basic setup of a simple ring cavity of Erbium doped fiber laser (EDFL) to a more advanced configuration which enables wavelength tunability by employing different wavelength selective elements including the tunable bandpass filter (TBF), arrayed waveguide gratings (AWG) and fiber Bragg gratings (FBG). Comparison on the Q-switching output performance using different wavelength selective elements is analysed. In addition, graphene Q-switched EDFL based on distributed Bragg reflector (DBR) cavity configuration and multiwavelength graphene Q-switched Brillouin-erbium fiber laser have been demonstrated as well, with each approach having their own advantages. Furthermore, a Q-switched EDFL based on graphene oxide as the saturable absorber with a simple deposition method has also been introduced. Apart from Q-switching, mode-locking generation based on graphene saturable absorber is also being demonstrated and investigated using a simple ring cavity EDFL. To provide the wavelength tunability of the mode locked EDFL, a TBF is inserted into the cavity as the tuning mechanism. Further investigation on the graphene based mode locked fiber laser is carried out by using an exotic and highly doped Zirconia-erbium doped fiber (Zr-EDF) as the gain medium. It is interesting to observe that beyond a certain pump power, harmonic mode locking takes place. In addition, by incorporating a Mach Zehnder filter into the cavity, the spectrum tunability of the mode locked Zr- EDFL is achieved and has been well demonstrated. Further development of this graphene based Zr-EDFL is carried out by demonstrating it as a pulse source for supercontinuum (SC) generation with an advantage of low cost, since only a short length of single mode fiber (SMF) is used as the nonlinear medium. Moreover, in this work, graphene has been also demonstrated as a saturable absorber for suppressing the noise and multimode oscillations in the laser cavity, and acts as the key enabler to produce the single longitudinal mode (SLM) operation in the EDFL. By heterodyning this SLM laser output and an external tunable laser source (TLS) at a photodetector, a tunable radio frequency generation can be realized.